Who Am I? Theorising Self(s) and Identity(s) in an Attempt to Self-explore. (July 2015) - Guha, Surangama
This article approaches the concepts of self and identity from the point of view of the author, contextualising them through the experiences of the author herself, while drawing from and substantiating these experiences in the light of prevailing discourses on self, identity, representation and diaspora. Through self-exploration, the author endeavours to find out whether or not it is possible to establish the existence of a true 'core self' that emerges through experience and at the site of popular representation; or whether what is experienced is not the 'true self' or identity but a broken and disjointed idea of the same. While fundamentally deriving from the theses of Hall and Bhabha, whose intellectual discourses originated from their own diasporic experiences, this article attempts to show, through self-exploration, how contemporary popular Hindi cinema pursues a nation-building project, as it constructs for its audience an image of 'India' and 'Indianness'.